Effect of Advertising on the Consumer Buying Behaviour of New Products in Ajinomoto Foods Nigeria Limited, Katsina-Nigeria - Abubakar, Ahmadu; Achuku, Alexander (Journal of Business & Management, 2023)
This study explores the effect of advertising on the consumer buying behaviour of new products (Delidawa & Madish) in Ajinomoto Foods Nigeria Limited, using 550 respondents drawn from different streets of Katsina town, Nigeria. The study adopts a cross-sectional survey research design, favouring the collected structured questionnaire at a single point in time. The study employed both descriptive and multiple regression techniques to analyze the data. The main findings of the research reveal that television advertising has a positive and statistically significant effect on consumer buying behaviour; radio advertising has a negative but significant effect on consumer buying behaviour, and outdoor advertising has no significant effect on the consumer buying behaviour of Delidawa and Madish products in the Katsina town. The study concludes that although advertisement mainly, through television, has the potential to create the needed awareness about a product, arouse consumer’s interest, and spark desires, which leads to the ultimate demand for a product, other factors such as elasticity of demand, price, quality of the product, income level and taste among others are also determining factors of the consumer buying behaviour for a product. The study recommends, among others, that Ajinomoto Foods Nigeria Ltd should increase the frequency of the television advertisement as doing so can enhance the consumer buying behaviour of the new products